Pengaruh Kualitas Pelayanan Terhadap Kepuasan Dan kepercayaan Pasien Rawat Inap Di rumah Sakit Umum Daerah Andi Makkasau Parepare: The Effect of Service Quality on Satisfaction and Confidence of Inpatients at the Andi Makkasar Regional General Hospital Parepare - Muhammad Taufiq; Samsualam Samsualam; Andi Surahman Batara (Program Pascasarjana Universitas Muslim Indonesia, 2022)
Background: Hospitals today must be able to provide services that are fast, accurate, quality and affordable, which can ultimately provide satisfaction in the results of care by the wishes, hospitals with good quality are very dependent on existing resources, such as the services of doctors, nurses, staff/employees and facilities and infrastructure available, including environmental safety, to create a sense of satisfaction and trust in the hospital. Method: This research uses this type of quantitative research using a cross-sectional design. The population in this study was hospital inpatient Andi Makkasau Parepare as many as 90 respondents. Sampling is done proportionate stratified random sampling. Result: There were 90 respondents involved in the study. Most of the respondents were in the 21-30 age group (35.6%), female (46.7%) Male (53.3%) IRT employment (38.9%) and S1 education (34.4%). Bivariate statistical test results showed that there was a 5-dimensional influence (Reliability, Responsiveness, Assurance, Empathy, and Tangibles) of Service Quality (p= 0.000 on the satisfaction and confidence of general inpatients at Andi Makkasau Parepare Hospital. Conclusion: The quality of service affects the satisfaction and trust of hospital inpatient Andi Makkasau Parepare. The free variable that most affects the satisfaction of hospital inpatients Andi makkasau is the Guarantee variable while trust is the guarantee variable.